Maintaining Funniness of Jokes Translated from Indonesian into English - Jehoshua Yeremia Putra Sutanto (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study is about translation of Indonesian jokes into English. This study is about maintaining the funniness of jokes in Indonesian when translated into Indonesian and the difficulties experienced while translating jokes. Mona Baker [2018] theory is used in this study. The difficulties found also varied, such as errors in word, above word, and grammar in humorous texts. To maintain the funniness of the jokes in English, the writer shifts the jokes after rereading and revising the translation.